Penguatan Budaya Literasi Membaca pada Anak di Era Disrupsi Teknologi melalui Pendirian Komunitas Baca di Teluk Purwokerto Selatan: Indonesia - Oktaviana, Ika; Lapiana, Ummi Nurjamil Baiti; Asriyama, Weksa Pradita; Junawaroh, Siti (UII, 2025)
The era of technological disruption poses challenges in fostering a culture of reading literacy among children. This community service endeavor aims to fortify the reading culture among children in Teluk, South Purwokerto, addressing the issue of waning interest in reading. The endeavor involves establishing a reading community to promote reading habits and create an engaging and supportive reading environment. By enhancing reading literacy culture, the objective is to establish a robust and enduring reading culture. The outcomes of this endeavor demonstrate that it not only succeeded in nurturing children's interest in reading but also improved their language skills and critical thinking abilities in Teluk, South Purwokerto.